https://doi.org/10.36873/ KESIAPAN MASYARAKAT UNTUK MENGEMBANGKAN INTENSIFIKASI USAHATANI PADI LADANG PADA LAHAN GAMBUT DI DESA TUWUNG KECAMATAN KAHAYAN TENGAH KABUPATEN PULANG PISAU PROVINSI KALIMANTAN TENGAH: Readiness Of The Community To Develop The Intensification Of Rice Field Business On Peat Land In Tuwung Village, Kahayan Tengah District, Pulang Kisau Regency, Central Kalimantan Province - Suharno Suharno; Trisna Anggreini; Siti Zubaidah; Eti Dewi Nopembereni (Fakultas Pertanian Universitas Palangka Raya, 2021)
The development of dryland rice farming on peatlands has great potential in order to increase national food production, especially rice. This research is a preliminary study or base line study of the action research on the intensification of upland rice on one hectare of peatland which was carried out in Tuwung Village, Kahayan Tengah District, Pulang Pisau Region of Central Kalimantan. This study aims to determine the technical and socio-economic potential and the readiness of the local community to participate in this activity. The research was conducted by exploring the opinions and responses of the local community through Focused Group Discussions (FGD) and digging up secondary data and information and appropriate literature. Tuwung village has great technical potential in the form of a fairly large land, which is 9,253 ha in the form of dry land in a peat swamp ecosystem supported by rainfall and an appropriate agro-climate for agricultural development. Currently, most of the land is in the form of rubber plantations, secondary forests and shrubs and shrubs from former cultivation that have been left uncultivated (not cultivated) for more than ten years, as well as river and oxbow lake areas, which are lakes formed from dead streams that have been formed by the river. Agricultural potentials that can be developed in this village include upland rice and secondary crops, horticulture (fruits and vegetables), animal husbandry, aquaculture (karamba) and forestry. The support and enthusiasm of the local community for the success of the study on the intensification of upland rice farming on peatlands in this village is very high, as evidenced by the establishment of a farmer group called the “Bawi Hapakat”, which is a women's farmer group. The farmer groups are the target of community development and empowerment and as direct beneficiaries of this activity